review of the ecology and management of Ranunculus acris subsp. acris in pasture - LAMOUREAUX, S.L; BOURDÔT, G.W (Weed research, 2007)
Ranunculus acris subsp. acris is widespread in pastures across Europe. In New Zealand, it persists in dairy pastures throughout the country, despite the annual use of herbicides, causing a loss in the national yield of milk solids estimated at NZ$156 million in the 2001-2002 milking season. Its persistence appears to be due in part to the production of a blistering agent, protoanemonin, which deters grazing animals, combined with evolved resistance to herbicides and a resilience imparted by a stout rhizome supporting dormant axillary buds. The latter enables regeneration after damage inflicted by herbicides, fungi and other control agents, and facilitates lateral spread and asexual reproduction. Its persistence in dairy pastures may also be influenced by plants recruiting from seeds which are formed annually subject to the availability of insect pollinators. Based on a review of observations and experiments conducted mainly in Europe and New Zealand, we propose a detailed life-cycle model for R. acris. This provides the basis for a matrix population model that will identify the life-cycle stages that contribute most to population growth and, hence, the extent to which each of these would need to be targeted for improved management in dairy pastures in New Zealand.